Implementasi Undang-Undang Nomor 25 Tahun 2009 tentang Pelayanan Publik pada Kantor Dinas Kependudukan dan Pencatatan Sipil Kabupaten Jember - Suhraeni Suhraeni; Nur Solikin (Sharia Faculty, Kiai Haji Achmad Siddiq State Islamic University of Jember, 2021)
The Department of Population and Civil Registration of Jember Regency is an agency tasked with recording the condition of the population quantity in Jember Regency, as well as serving the community in obtaining official Population and Civil Registration Documents. In this study using a descriptive analysis approach and the type of research used is qualitative. Then the data collection used is by observation, interviews, and documentation. The data validity technique used triangulation technique. The conclusions of this study are: (1) the Department of Population and Civil Registration of Jember Regency has not made every effort to provide public services in accordance with the principles of public services contained in Law Number 25 of 2009 including the Principles of Professionalism, the Principle of Punctuality, and Principles (2) supporting factors that influence the success of public services at the Department of Population and Civil Registration of Jember Regency, namely: Human Resources (HR), Financing Resources, Adequate Facilities and Infrastructure, Information Technology, and Legislation Policy (3 ) inhibiting factors that affect public services at the Department of Population and Civil Registration of Jember Regency, namely: Cultural factors (use of brokers and illegal fees), Community Awareness Factors, and Lack of responsiveness of officers to the community.